Heritage interpretation : educational and recreational management for the valuation of the natural and cultural legacy of the Alameda Park - Cevallos Becerra, Renato Gustavo (2020)
La Alameda Park is the oldest park in the city of Quito; it is part of the heritage protection area that has a variety of tangible and intangible natural and cultural attractions of heritage and emblematic categorization that are part of the identity of the Quiteño. However, the scarce information and recreational-educational activities related to its attractions have turned it into a park of passage. For this reason, the design of an interpretive program with recreational-educational activities is a management tool for the valuation and conservation of the place and the dissemination of cultural tourism. In the process of collecting information, observation sheets and semi-structured interviews were used with focus groups made up of visitors, neighbors and key actors to establish the use, knowledge and importance of the attractions; in addition to establishing the profile of the potential visitor. Thus, through research and analysis, three potential attractions were identified (heritage trees, emblematic fauna and the history of the Alameda Park) and two interpretive activities (puppet shows and storytelling), which act as mediating tools between society and its heritage, awakening interest in knowing the natural and cultural environment in an innovative and creative way, as well as responding to the needs of visitors.